ESTO NO ES UNA ELEGÍA. POÉTICA Y ECONOMÍA DE LA CLASE MEDIA COSTARRICENSE EN EL SIGLO XX. - García, George I. (2009)
Through a periodization related to the history of world capitalism, this essay deals about the discoursive changes regarding social differentiation in Costa Rica, and particularly the topic of the middle class, along the twentieth century.